I am reading book concrete mathematics, author talks about general method of converting recurrence relation of type $$a_nT_n=b_nT_{n−1}+c_n$$

multiplies the above relations with $s_n$ called summation factor.

which makes the equation : $$s_na_nT_n=s_nb_nT_{n−1}+s_nc_n$$

such that $$s_nb_n=s_{n−1}a_{n−1}$$

making $S_n=s_na_nT_n$ so $$S_n=S_{n-1}+s_nc_n$$ what i didn't understand is he write that $$S_n=s_0a_0T_0+\sum_{k=1}^{n}{s_kc_k}=s_1a_1T_0+\sum_{k=1}^{n}{s_kc_k}$$ how?


Just note that

$$ S_n - S_{n-1} =s_n c_n$$

Summing from $1$ to $n$ it gives :

$$S_n - S_0 = \sum_{k=0}^n s_k c_k $$

(see telescoping sums). Given that $S_0 = s_0a_0T_0$ and $s_1b_1 = s_0a_0$ you finally have :

$$S_n=s_0a_0T_0+\sum_{k=1}^{n}{s_kc_k}=s_1 b_1T_0+\sum_{k=1}^{n}{s_kc_k}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.